Balanço hídrico na sub-bacia hidrográfica do Boi Branco – SP para gestão sustentável da agricultura irrigada - Sales, Mariana Alexandre de Lima [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The water resources are fundamental to the development of several economic activities. Concerning the agriculture production, the water can represent close to 90% of the physical constitution of the plant. The low water supply during the growing stage of vegetables can make the agricultural production not viable and can even seriously affect the balance of the ecosystem. One way to calculate the amount of water in a determined system is by means of the water balance, that is an important tool for the assessment process of the water cycle in a specific region or specific crop, as it represents the sum of water quantity that gets in and out of a given system, in a given time range, whose result indicates - during the assessed period - if there is a shortage or excess of water for the crop. Its importance is essential for the studies on the water regime, agriculture planning, zoning, climate studies, among other uses. The main goal of this work was to establish the water balance in the watershed Boi Branco-SP, so that it can be used as a tool for the hydro-agricultural and environmental planning of the region. The water climate balance in a monthly scale was determined with the aim to recognize the water availability in the region. It was also determined the water balance of tillage for the irrigation control in the different crops of the watershed, aiming to verify the most critical periods of low water supply in the soil, making it possible a better water management. The required data for water balance calculation are the precipitation, evapotranspiration, given by the installed crop and water holding capacity in the soil (WHC). For the water climate balance, it was used data of the historical series of the region, available in pluviometric stations located in the studied area. It was ...

Os recursos hídricos têm importância fundamental no desenvolvimento de diversas atividades econômicas. Em relação à produção agrícola, a água pode representar até 90% da constituição física das plantas. A falta d’água em períodos de crescimento dos vegetais pode inviabilizar a produção agrícola e até afetar seriamente ecossistemas equilibrados. Uma das formas de se contabilizar a quantidade de água em determinado sistema é por meio do balanço hídrico, que se constitui de uma importante ferramenta para o processo de avaliação do ciclo da água em uma determinada região ou determinada cultura, visto que representa o somatório das quantidades de água que entram e saem de um dado sistema, em um determinado intervalo de tempo, cujo resultado indica durante o período avaliado se há deficiência ou excedente hídrico para a cultura. Sua importância é indispensável para estudos sobre o regime hídrico, planejamento agrícola, zoneamento agrícola, estudos climáticos, entre outras aplicações. O objetivo central deste trabalho foi determinar o balanço hídrico na sub-bacia hidrográfica do Boi Branco-SP, para servir como ferramenta ao planejamento hidroagrícola e ambiental da região. O balanço hídrico climatológico na escala mensal foi determinado com a finalidade de se conhecer a disponibilidade hídrica da região. Determinou-se também o balanço hídrico de cultivo para o controle de irrigação, nas diversas culturas da sub-bacia com o intuito de verificar os períodos mais críticos de deficiência hídrica no solo, possibilitando um melhor manejo da irrigação. Os dados requeridos para o cálculo do balanço hídrico são os de precipitação, evapotranspiração, dados da cultura instalada e capacidade de armazenamento de água no solo (CAD). ...
Keywords: Agua na agricultura; Planejamento agricola; Evapotranspiração; Water in a agriculture